Biomimetic scaffolds and dynamic compression enhance the properties of chondrocyte‐ and MSC‐based tissue‐engineered cartilage. (25th March 2018) - Sawatjui, Nopporn; Limpaiboon, Temduang; Schrobback, Karsten; Klein, Travis
Abstract: Adult chondrocytes are surrounded by a protein‐ and glycosaminoglycan‐rich extracellular matrix and are subjected to dynamic mechanical compression during daily activities. The extracellular matrix and mechanical stimuli play an important role in chondrocyte biosynthesis and homeostasis. In this study, we aimed to develop scaffold and compressive loading conditions that mimic the native cartilage micro‐environment and enable enhanced chondrogenesis for tissue engineering applications. Towards this aim, we fabricated porous scaffolds based on silk fibroin (SF) and SF with gelatin/chondroitin sulfate/hyaluronate (SF‐GCH), seeded the scaffolds with either human bone marrow mesenchymal stromal cells (BM‐MSCs) or chondrocytes, and evaluated their performance with and without dynamic compression. Human chondrocytes derived from osteoarthritic joints and BM‐MSCs were seeded in scaffolds, precultured for 1 week, and subjected to compression with 10% dynamic strain at 1 Hz, 1 hr/day for 2 weeks. When dynamic compression was applied, chondrocytes significantly increased expression of aggrecan ( ACAN ) and collagen X ( COL10A1 ) up to fivefold higher than free‐swelling controls. In addition, dynamic compression dramatically improved the chondrogenesis and chondrocyte biosynthesis cultured in both SF and SF‐GCH scaffolds evidenced by glycosaminoglycan (GAG) content, GAG/DNA ratio, and immunostaining of collagen type II and aggrecan. However, both chondrocytes and BM‐MSCs cultured in SF‐GCH scaffolds under dynamic compression showed higher GAG content and compressive modulus than those in SF scaffolds. In conclusion, the micro‐environment provided by SF‐GCH scaffolds and dynamic compression enhances chondrocyte biosynthesis and matrix accumulation, indicating their potential for cartilage tissue engineering applications.